Study on The Implementation of The Regulations of Terrorism Activities In Social Media - Basari, Angga Dewanto; Syauqillah, Muhammad; Ismail, Asep Usman (UI Scholars Hub, 2020)
The legal scope of the Terrorism Law and the Information and Electronic Transactions Law in Indonesia is considered as lacking to cover the problem of cybercrime in social media. Aside from literature review, this paper is also supported by data from direct interview with the Head of Counterterrorism Special Detachment 88 (Densus 88 AT) of Indonesian National Police. The data found out that the Terrorism Law is a repressive response towards terrorism crimes that have already occured, but less preventive to future crimes. The existence of laws in Indonesia is often one step behind its crime. The difference of perception in seeing a crime also becomes a shortcoming for the legal apparatus, but becomes an opportunity for perpetrators of the crime. Prevention needs to be done as a form of monitoring and controlling the contents that could lead to the criminal acts of terrorism.